Ustanovitev "Yugoslav Emergency Council" v New Yorku - Vovko, Andrej (Zgodovinski časopis, 1987)
After the German attack on Yugoslavia the representatives of the Yugoslav emigrants agreed on their meeting on 14th of April 1941 in New York to establish a special organisation to help the old homeland. This organisation, named "Yugoslav Emergency Council", in many ways presented the continuation ofwork of a similar in 1935 established organisation "Defence Alliance for Yugoslavs in Italy" (also similar considering members). The Yugoslav Emergency Council prepared in cooperation with Czehoslovakian associations on the 2nd of May 1941 a mass meeting as a support to the occupied Yugoslavia. With its first meeting of members on the 2nd of June 1941 the Yugoslav Emergency Council tried to place its activity on a wider basis - to involve all Yugoslav emigrants, individuals and organisations throughout the USA, Canad and South America. The rules accepted on the first member meeting foresaw political aid for the restoration of the State of Yugoslavia following the USA pattern of political and economical democracy. The note of the beginning of this organisation is based on records of its sessions brought from the USA
Keywords: druga svetovna vojna; emigration; history of Yugoslavia; izseljeništvo; second world war; zgodovina Jugoslavije